Optimizing Antiretroviral Therapy in Treatment-Experienced Patients Living with HIV: A Critical Review of Switch and Simplification Strategies. An Opinion of the HIV Practice and Research Network of the American College of Clinical Pharmacy. (11th September 2019) - Chastain, Daniel; Badowski, Melissa; Huesgen, Emily; Pandit, Neha Sheth; Pallotta, Andrea; Michienzi, Sarah
Simplifying or switching antiretroviral therapy (ART) in treatment-experienced people living with HIV (PLWH) may improve adherence, tolerability, toxicities, and/or drug–drug interactions. The purpose of this review is to critically evaluate the literature for efficacy and safety associated with switching or simplifying ART in treatment-experienced PLWH. A systematic literature search using MEDLINE was performed from January 1, 2010 to April 30, 2018. References within articles of interest, the Department of Health and Human Services guidelines, and conference abstracts were also reviewed. Switch/simplification strategies were categorized as those supported by high-level clinical evidence and those with emerging data. Rates of virologic suppression were noninferior for several switch/simplification strategies when compared to baseline ART. Potential for reducing adverse events was also seen. Additional evidence for some strategies, including most 2-drug regimens, is needed before they can be recommended.